Toward Universal Coverage in Health : The Case of the State Guaranteed Benefit Package of the Kyrgyz Republic - Giuffrida, Antonio; Jakab, Melitta; Dale, Elina M. (World Bank, Washington DC, 2013)
In this case study the paper describes the evolution of the Kyrgyz health care system and discusses challenges in ensuring universal access to basic health care services. Section one provides an overview of the Kyrgyz health system and of the national health care reform programs that started in 2001 with Manas (2001-2005) and which have been continued with Manas Taalimi (2006-2011), and the recently adopted Den Sooluk (2012-2016). Section two provides a detailed discussion of the SGBP that follows a universal approach as it applies to all citizens, and describes the management of public funds and the information environment of the State Guaranteed Benefit Package (SGBP). Section three draws lessons from Kyrgyz national health reforms for universal health coverage for other countries with very limited public resources, widespread poverty, and high levels of corruption. Section four discusses the remaining challenges for universal health coverage for the poor and how the provision of good-quality care forms an important part of the agenda for the recently adopted Den Sooluk program.